Prosody and discourse structure in Buenos Aires Spanish - Omar Labastía, Leopoldo; Eva Dabrowski, Alejandra; Ángeles Guglielmone, María de los (Revista Leitura, 2014)
In previous work, we examined the role of some prosodic features in structuring spoken discourse. In this paper, we explore monologue in political discourse, and attempt to link these prosodic cues to the speaker’s argumentative goals. The prosodic analysis is carried out in the Autosegmental-Metrical framework applied to Buenos Aires Spanish. The pragmatic analysis follows Relevance Theory. Tonal configurations guide the hearers to those parts of the discourse the speaker wants the audience to consider highly relevant. DOI: 10.28998/2317-9945.2013v2n52p227-247